Infrared Thermographic Testing of Hybrid Materials Using High-Power Ultrasonic Stimulation; Russian Journal of Nondestructive Testing; Vol. 54, iss. 10 - Derusova D. A. Dariya Aleksandrovna; Vavilov V. P. Vladimir Platonovich; Guo Xingwang; Shpilnoy V. Yu. Viktor Yurjevich; Danilin N. S. (2018, 2018)
Title screen